Front Cover: Physiologically‐Based Kinetic Modeling Predicts Similar In Vivo Relative Potency of Senecionine N‐Oxide for Rat and Human at Realistic Low Exposure Levels. Issue 4 (21st February 2023) - Widjaja, Frances; Alhejji, Yasser; Yangchen, Jamyang; Wesseling, Sebastiaan; Rietjens, Ivonne M. C. M.
Abstract : Mol. Nutr. Food Res . 2023, 67, 202200293 DOI: 10.1002/mnfr.202200293 Pyrrolizidine alkaloid N‐oxide (PANO), a common plant‐based food protoxin, can be reduced to pyrrolizidine alkaloid (PA) by liver S9 and gut microbiota, causing liver toxicity and carcinogenicity. In article number 2200293, Frances Widjaja and co‐workers used new approach methodologies to predict the relative potency (REP) of PANO to PA in both rats and humans at low and high dose levels.